Semantic Field of “Spirituality”: Lexical Analysis and Psychological, Philosophical Features - Bahodirovna, Akhmedova Mehrinigor (European Journal of Life Safety and Stability (2660-9630), 2022)
This article deals with the revealing spirituality concept and its analysis in different spheres, especially, in religion, psychology and philosophy. The main theme is to analyse this concept semantically and lexically.